Formation of cross-functional teams and other economic and management reengineering measures of business processes in the context of implementing innovative initiatives in construction companies - Petrukha, N.; Omelchuk, R.; Rizun, D.; Bilous, B.; Lytarev, O. (Ways to Improve Construction Efficiency, 2023)
In the current conditions of development of construction enterprises, significant attention is paid to innovative measures that contribute to improving their efficiency and competitiveness. One of the important aspects of this process is the formation of cross-functional teams that are able to integrate various specialized knowledge and experience to solve complex problems within business processes. The creation of such teams is part of economic and managerial reengineering, which is focused on optimizing and transforming business processes to increase their effectiveness and adapt to new conditions. Business process reengineering involves not only technical changes, but also a significant organizational transformation, which includes improving the management structure, interaction between departments, as well as adopting innovative approaches to project and resource management. The introduction of innovative measures into construction processes is aimed at increasing productivity, reducing costs and improving the quality of results. Therefore, the correct organization and functioning of cross-functional teams is an important factor in the successful implementation of innovations in the enterprise. This approach allows for a comprehensive consideration of issues related to project management, the use of new technologies and methods, which are important for the effective operation of construction companies in a modern dynamic environment. The integration of various management approaches, such as the use of modern digital technologies (BIM, IoT, Big Data, AI) in combination with traditional methods, allows construction companies to increase efficiency, reduce risks and achieve better financial results. The implementation of innovative strategies based on such an integrated approach allows enterprises not only to optimize their business processes, but also to significantly increase their competitiveness in the construction market. In addition, the successful implementation of innovations can lead to a reduction in environmental impact and increased safety, which are also important aspects for the sustainable development of the construction sector. This allows for the efficient use of resources, to achieve maximum impact on quality and safety, and to reduce the cost of construction.